The Effect of Syllable Method on Early Reading Skills of Second Grade Students at SDN 185 Palembang - Agustin, Winda; Mardiah Astuti; Siti Fatimah; Ahmad Syarifuddin; Miftahul Husni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the early reading skills of students who were taught using the syllable method, as well as those who were not taught using this method, and to assess the effect of the syllable method on students' early reading skills. This is a quantitative research using a true experimental design, specifically a pretest-posttest control group design. The sample was determined using probability sampling, specifically simple random sampling, where the sample group is selected randomly without considering strata in the population. Thus, the sample in this study consists of 56 students. The data collection techniques used in this study include tests (oral tests) and documentation, while the data analysis techniques involve validity and reliability tests, as well as hypothesis testing (Independent Sample T-Test) using Ms. Excel and SPSS IBM version 30 for Windows. The results of the study are as follows: (1) The early reading skills of the control group students were adequate, as indicated by the early reading skill indicators, which showed slight improvement, although not all students showed good early reading skills due to many scores falling below the Minimum Passing Criteria (KKM). The pretest average score was 10.928 with an average score of 54.642, while the posttest average score was 11.857 with an average score of 59.464. (2) The early reading skills of the experimental group students were very good, as seen from the indicators of early reading skills, which showed significant improvement, and all students in this group scored above the KKM. The pretest average score was 12.000 with an average score of 60.000, while the posttest average score was 15.321 with an average score of 76.607. (3) The syllable method had a significant effect on students' early reading skills, as indicated by the hypothesis test (Independent Sample T-Test), where the significance value was 0.001 < 0.05, meaning Ha is accepted and Ho is rejected. This shows that the syllable method has an effect on the early reading skills of second-grade students in Bahasa Indonesia at SDN 185 Palembang.